P-XRF analysis of multi-period Impasto and Cooking Pot wares from the excavations at Stromboli-San Vincenzo, Aeolian Islands, Italy. Issue 2 (15th December 2017) - Cannavò, Valentina; Photos-Jones, Effie; Levi, Sara Tiziana; Brunelli, Daniele; Fragnoli, Pamela; Lomarco, Giacomo; Lugli, Federico; Martinelli, Maria Clara; Sforna, Marie Catherine
ABSTRACT: This exploratory study focuses on the elemental analysis by p-XRF (portable X-Ray Fluorescence Analyser) of 62 samples of coarse wares, consisting of Bronze Age handmade burnished ware, so-called Impasto, and of Cooking ware (dated from the Roman period to Modern times). All wares originate from the site of San Vincenzo, Stromboli, and Aeolian Islands. The question addressed here is whether it is possible to differentiate between local (Aeolian) and imported (non-Aeolian) fabrics with the use of the p-XRF; 42 of the 62 samples were also subjected to petrographic analysis as a way of testing our hypothesis. Our results show that p-XRF analysis can clearly assist in distinguishing between Aeolian vs. non-Aeolian wares. Analyses can take place in the field and large quantities of sherds can be processed as a result. We suggest that no further demands should be made of the technique in providing answers to more detailed provenance questions. This is because finer separation in subgroups (as achieved recently by combined petrographic and EPMA analysis on select samples) is not possible given the nature of coarse pottery and the limitations of the technique in measuring key light elements (Na, Mg). Furthermore, for some elements (e.g Cr) accuracy is below acceptable levels in which case results for these particular elements are considered semi-quantitative.